The Influence of Competence, Motivation, Loyalty, and Work Discipline on the Productivity of North Kalimantan Regional Police - Ambar Vitaningrum; Rina; Hafipah (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This study aims to analyze the effect of competence, motivation, loyalty, and work discipline on the productivity of members of the Regional Police of North Kalimantan province. This research used a descriptive research approach and a causal design approach. The population in this study was 3,294 police officers, and the sample used the Krejci table. The analysis technique used is multiple regression analysis through the SPSS 22 program. The results showed that competency had a positive and significant effect on the work productivity of North Kalimantan Regional Police members, motivation had no effect on the work productivity of North Kalimantan Regional Police members, loyalty had no effect on the work productivity of North Kalimantan Regional Police members, and discipline had a positive and significant effect on the work productivity of North Kalimantan Police members.